Efficient Motion Field Interpolation Method for Wyner-Ziv Video Coding - I Made Oka Widyantara; Wirawan Wirawan; Gamantyo Hendrantoro (Universitas Ahmad Dahlan, 2011)
Wyner-Ziv video coding has the capability to reduce video encoding complexity by shifting motion estimation procedure from encoder to decoder. Amongst many motion estimation methods, expectation maximization algorithm is the most effective one. Unfortunately, the implementation of block-based motion estimation in this algorithm causes motion field profile bounded by granularity of block size. Nearest-neighbor and bilinear interpolation methods have already applied in multiview image coding to handle similar problem. This paper aims to evaluate performance of both interpolation methods in transform-domain Wyner-Ziv video codec. Results showed that bilinear interpolation effective only for high motion video sequences. In this scenario, it has bitrate saving up to 3.29 %, 0.2 dB higher PSNR, and 12.30 % higher decoding complexity compared to nearest-neighbor. In low motion video content, bitrate saving only gained up to 0.82%, with almost the same PSNR, while decoding complexity increase up to 10.32%.